Analisis Manajemen Konstruksi Pada Pembangunan Ruas Jalan Rate-Rate Dalam Kota - Nuhun, Ridwan Syah; Soeparyanto, Try Sugiyarto; Sutrayasa, Gede Agus; Deny, Laode; Ramadan, Kadir; Sulistyo, Galih Adi (Universitas Sulawesi Tenggara, 2024)
Road infrastructure development is an important factor in supporting economic growth and community mobility in urban areas. However, road construction in urban areas is often faced with various challenges, such as limited space, population density and the dynamics of community activities. This requires effective and efficient construction management to ensure the smoothness and success of the project. The aim of this research is to find out how cost calculations are carried out using AHSP and also to find out how to carry out and time schedule construction work for inner city lane roads. The method for implementing the construction of lane roads in the city is in the form of asphalting roads with a length of 3.06 KM and a duration of 90 days. The budget plan for building a 3.6 KM inner-city toll road is IDR. 10,428,920,000.